A Paravenous Approach for the Saphenous Nerve Block. Issue 6 (1st November 2001) - De Mey, Jean-Claude J.; Deruyck, Ludwig J.; Cammu, Guy; De Baerdemaeker, Luc E.; Mortier, Eric P.
Abstract : Background and Objectives: This study assesses a paravenous approach for saphenous nerve block at approximately the level of the tibial tuberosity, and compares it with the conventional technique of blind subcutaneous infiltration between the tibial tuberosity and the gastrocnemius muscle. Methods: In dissections of 5 cadavers, the saphenous nerve was found very close to the saphenous vein bilaterally. Subsequently, in 20 volunteers, a bilateral saphenous nerve block was performed with 5 mL mepivacaine on each side. Randomly assigned, the block was performed by blind subcutaneous injection using a 23-gauge needle of 2.5 cm on one side and by a paravenous subcutaneous approach on the other. Results: The paravenous approach produced a saphenous nerve block in all 20 volunteers whereas the blind subcutaneous approach was successful in only 6 (33%) ( P < .05). Seven volunteers had a painless minor hematoma at the paravenous site and 2 had a hematoma at the classical site. Conclusion: The saphenous nerve can be blocked effectively by a paravenous approach using only 5 mL of local anesthetic solution. This approach is advantageous because of its easily identifiable landmark.